Kewenangan Pengawasan Ketenagakerjaan UPTD Kota Serang dan Kota Cilegon dalam Mengawasi Perlindungan Jaminan Sosial Pekerja ditinjau Berdasarkan Peraturan Menteri Ketenagakerjaan No. 33 Tahun 2016 - Ghaffar, Afan; Ikomastussuniah; Rayhan, Ahmad (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
The manpower agency cooperates with the Regional Technical Implementation Unit (UPTD) for Manpower Supervision. The identification of problems in this study, namely how the implementation of the authority of manpower supervisory employees and the obstacles to the implementation of authority faced by the Cilegon City and Serang City Supervision UPTD of the Banten Province Manpower and Transmigration Agency in implementing its authority in the Protection of Guarantees for outsourced workers in Banten Province. The theory used in this study is the theory of authority and the theory of law enforcement. The method used is the empirical legal approach method with a qualitative and descriptive type of research. The data sources used are primary and secondary data. The data collection technique for this study is field research and librarianship. The results of the study on the authority of labor supervision related to social security protection for outsourced workers are very important to ensure that companies fulfill their obligations in accordance with the law. The UPTD Labor Inspection has a crucial role in monitoring, inspecting, and enforcing the law to protect workers' rights. The implementation of the authority of labor inspectors in supervising social security protection for outsourced workers faces various significant obstacles. The obstacles faced by labor inspectors are the lack of knowledge of outsourcing service providers about social security obligations, data inconsistency between companies and related agencies, and workers' lack of awareness of their rights.